Neutrophil-to-lymphocyte ratio and survival outcomes in testicular cancer: A systematic review and meta-analysis - Campos-Aspajo, Alvaro (2024)
Background: The neutrophil-to-lymphocyte ratio (NLR) is a biomarker in inflammatory processes associated with multiple unfavorable outcomes in various diseases. This study aims to evaluate the association between NLR values and survival outcomes in patients diagnosed with testicular cancer. Methods: A systematic search was conducted in 6 electronic databases to retrieve studies evaluating NLR in patients with testicular cancer. The outcomes sought were overall survival (OS) and progression-free survival (PFS), and the effect measures were hazard ratio (HR) with a 95% confidence interval (CI). A random effects model was used for the meta-analysis. The risk of bias included in the studies was assessed according to the Newcastle–Ottawa Scale criteria. Egger test and Trim-and-fill method were used to test the publication bias among articles. Results: Six cohort studies (n= 1315) were evaluated. High NLR values are associated with a higher risk of OS (HR: 1.75; 95% CI 1.04 – 2.92, I2: 65%). However, no statistically significant association was found between NLR and PFS values. We found publication bias in the association between NLR and OS (Egger test < 0.1). This bias was corrected by using the trim- and-fill method (HR: 1.38, 95% CI 0.85 – 2.22) Conclusions: High NLR values are associated with worse OS; however, this result had publication bias, and the association was lost when this bias was corrected. Furthermore, no statistically significant association was found between NLR values and PFS.